Implementasi Manajemen Risiko pada Institusi Pendidikan Kedinasan: Persepektif Auditor Internal - Ita Masita; Frita Ayu Sistyana Putri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explore the implementation of risk management in higher education from the perspective of internal auditors. It describes how risk management is applied, particularly in government-affiliated higher education institutions. This research uses an interpretive case study approach conducted at a state-managed educational institution in Indonesia. The researchers explored the implementation of risk management through data collection methods such as interviews, participant observation, and document analysis. Risk management implementation has not been effective, as indicated by the risk maturity level being at level 2 (risk aware). This is due to risk management not yet being an organizational priority. Several challenges hinder effective risk management, including the absence of a dedicated risk management structure or unit, low understanding and awareness of the importance of risk management, limited human resources, and the lack of comprehensive risk management practices based on established standards such as ISO 31000:2018. As a result, not all organizational risks—such as fraud, tax miscalculation, asset risks, and others—are adequately addressed. This study requires a broader scope by involving multiple research objects and is limited by the availability of source documents, which require approval or special access. The research is valuable for leaders and managers in higher education in understanding the importance of risk management, helping them formulate policies to support effective risk management. It is also beneficial for enhancing the role of internal audit by identifying potential causes of deficiencies in risk management.